2008
DOI: 10.1074/jbc.m709350200
|View full text |Cite
|
Sign up to set email alerts
|

β-Fructofuranosidase Genes of the Silkworm, Bombyx mori

Abstract: Mulberry latex contains extremely high concentrations of alkaloidal sugar mimic glycosidase inhibitors, such as 1,4-dideoxy-1,4-imino-D-arabinitol (D-AB1) and 1-deoxynojirimycin (DNJ).Although these compounds do not harm the silkworm, Bombyx mori, a mulberry specialist, they are highly toxic to insects that do not normally feed on mulberry leaves. D-AB1 and DNJ are strong inhibitors of ␣-glucosidases (EC 3.2.1.20); however, they do not affect the activity of ␤-fructofuranosidases (EC 3.2.1.26). Although ␣-gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 29 publications
(38 reference statements)
3
70
0
Order By: Relevance
“…B. mori acquired the first gene from a bacterium or an ancestral baculovirus and the latter gene from a bacterium [8,9]. The results suggested that both genes bestow a clear selective advantage to B. mori .…”
Section: Resultsmentioning
confidence: 99%
“…B. mori acquired the first gene from a bacterium or an ancestral baculovirus and the latter gene from a bacterium [8,9]. The results suggested that both genes bestow a clear selective advantage to B. mori .…”
Section: Resultsmentioning
confidence: 99%
“…Until recently, b-fructofuranosidases were thought to be absent from animals despite being found among bacteria, fungi, and plants. However, pairs of these proteins have been identified in several lepidopteran species, apparently having arisen via horizontal transfer from bacteria (Daimon et al, 2008). Previously, these b-fructofuranosidases have primarily been associated with larval gut, so their presence in adult saliva is consistent with a role in digestion but also marks a distinct expansion of their known functional milieu.…”
Section: Carbohydrate Hydrolysismentioning
confidence: 96%
“…A common feature of cuticle and silk gland is that both of them have a chitin layer. Chitin and chitin‐binding cuticular proteins together form the chitin layer, which improves the defense ability of insects but at the same time limit their growth . The renewing of the chitin layer in the cuticle is well known, but the renewing of the chitin layer in the silk gland remains unclear.…”
Section: Introductionmentioning
confidence: 99%